An Empirical Analysis of Factors Influencing Fishermen’s Net Income: Evidence from Jawai Laut Village, Indonesia - Nurkholis, Faris; Kurniati, Dewi; Imelda, Imelda (Jambura Agribusiness Journal, 2025)
Indonesia is recognized as an archipelagic state with vast marine resources, covering approximately 3.1 million km² or about 62% of the total national territory, presenting significant potential for fisheries development. However, traditional fishermen face various challenges, including declining fish catches due to overfishing, rising input costs, expensive fishing equipment, and environmental degradation, all of which directly affect their net income and welfare. This study aims to analyze the factors influencing fisherman’s net income in Jawai Laut Village, South Jawai Subdistrict, Sambas Regency. The study employs a quantitative approach using primary data collected from 54 motorboat owning fishermen through structured interviews and questionnaires, complemented by secondary data from relevant institutions. The data were analyzed using a log-linear Cobb-Douglas net income model to estimate the elasticity of net income with respect to input cost variables, namely diesel prices, oil price, bait price, and labor wages. The results indicate that all input cost variables significantly affect fishermen’s net income. Diesel price, bait price, and labor wages have a positive and significant effect, while oil price has a negative and significant effect. The model demonstrates strong explanatory power, with a coefficient of determination (R²) of 0.868. These findings highlight the critical role of input cost dynamics in shaping fishermen’s economic performance. Therefore, policies related to stabilizing fuel prices, ensuring input availability, and improving cost efficiency are essential to enhance the welfare of small scale fishermen in coastal communities such as Jawai Laut Village.